Privacy and Personal Data Protection in Electronic Voting: Factors and Measures - Muharman Lubis; Mira Kartiwi; Sonny Zulhuda (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2017)
In general, electronic voting as the technology advancement offers the opportunities to reduce the time and budget of implementation which present the greater advantages than traditional approach. It seeks establish the privacy framework in the context of electronic voting that aligns with the mutual comprehension of relevant factors and measures. The result found that privacy concern and perceived benefit have influenced personal data protection significantly. The success and failure of electronic voting implementation depend on the fulfilment of the voter needs on privacy and personal data protection.